2018
DOI: 10.1155/2018/9141746
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Role of Ultrasound Guided Percutaneous Laser Ablation in Elderly Unresectable Breast Cancer Patients: A Feasibility Pilot Study

Abstract: Background and Objectives Breast-conserving surgery represents the standard of care for the treatment of small breast cancers. However, there is a population of patients who cannot undergo the standard surgical procedures due to several reasons such as age, performance status, or comorbidity. Our aim was to investigate the feasibility and safety of percutaneous US-guided laser ablation for unresectable unifocal breast cancer (BC). Methods Between December 2012 and March 2017, 12 consecutive patients underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The laser technology had broad clinical application in many diseases, such as unresectable breast cancer 18, renal tumor 19, hepatocellular carcinoma (HCC) 20, thyroid nodule 21, 22 and, more advanced, photodynamic cancer therapy 23, 24. Since US-guided LA was applied in PTMC firstly by Papini et al 10, four more articles were written about LA 9, 17, 25, 26.…”
Section: Us-guided Laser Ablation (La)mentioning
confidence: 99%
“…The laser technology had broad clinical application in many diseases, such as unresectable breast cancer 18, renal tumor 19, hepatocellular carcinoma (HCC) 20, thyroid nodule 21, 22 and, more advanced, photodynamic cancer therapy 23, 24. Since US-guided LA was applied in PTMC firstly by Papini et al 10, four more articles were written about LA 9, 17, 25, 26.…”
Section: Us-guided Laser Ablation (La)mentioning
confidence: 99%
“…Complete ablation rate assessment and follow-up were performed with US and mammography in the study without resection. 53 No local recurrences (0%, 95% CI, 0%-24%) were seen in 12 patients after 6 to 51 months (median 28.5 months) of follow-up with US and mammography. 53 Other Subgroup Analyses.…”
Section: Methods Of Determining Complete Ablation and Timing Of Resectionmentioning
confidence: 88%
“…53 No local recurrences (0%, 95% CI, 0%-24%) were seen in 12 patients after 6 to 51 months (median 28.5 months) of follow-up with US and mammography. 53 Other Subgroup Analyses. Newer studies reported higher complete ablation rates (85.9%, 95% CI, 70%-94%) than studies performed before 2009 (40.7%, 95% CI, 5%-90%) and between 2009 and 2016 (50.0%, 26%-74%; Q = 7.06, P = .029).…”
Section: Methods Of Determining Complete Ablation and Timing Of Resectionmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, there are also studies on the laser thermal ablation of benign lesions, such as fibroadenomas 16 , 17 or as palliative therapy in inoperable or refusing surgery patients. 18 …”
Section: Introductionmentioning
confidence: 99%